Carbonate grain associations: their use and environmental significance, a brief review - Kindler, P.; Wilson, Moyra (International Association of Sedimentologists (IAS) Special Publication 42, Blackwell Publishing Ltd., 2010)
A complex interplay of environmental factors may affect regionally important Cenozoic carbonate deposits, and a combination of different controls may result in comparable deposits. There is, therefore, a need for purely descriptive nomenclature to defineregionally extensive groupings of carbonate deposits. This terminology is reviewed here. In addition to the well-established chlorozoan (or coralgal), chloralgal, foramol, rhodalgal, molechfor and bryomol definitions, two new terms, LB-foralgal and thermacor,are proposed. These purely descriptive groupings allow for good spatial and temporal subdivision of Cenozoic carbonate deposits. The continued use of objective terms for Cenozoic carbonate deposits does not preclude the use of other interpretative grain-association terminology, and a two-tier system might be adopted. However, it should be clearly stated when groupings based on benthic components are being used purely descriptively, and therefore in an objective sense. It is hoped that this descriptive approach to regionally important deposits will help to promote objective discussions about controls on carbonate sedimentation and environmental change during the Cenozoic.